Recurrent respiratory tract infections in young children : the use of pediatric Tuina in southern China - Lingjia Yin (2025)
Background: Young children are particularly vulnerable to recurrent respiratory tract infections (RRTIs), which are associated with significant morbidity and mortality. When children experience RRTIs, caregivers face the dual challenge of preventing new episodes while maintaining a close relationship with their child. In China, medical pluralism is widely practiced, with caregivers often seeking treatment from both biomedicine and Chinese medicine. One commonly used Chinese medicine practice is pediatric Tuina (PT), a gentle massage technique performed by trained providers, which has long been used as a preventive approach against respiratory infections. When seeking healthcare for children with RRTIs, caregivers have their specific concerns and preferences. However, little is known about the use of PT in children's RRTIs from the clinical, caregiver, and practitioner perspectives.Aims: To enhance understanding of the use of PT in young children with RRTIs in Southern China.Methods: Both quantitative and qualitative approaches were employed. Study I involved a cohort of 2303 children with RRTIs. Data were extracted from electronic medical records. Children were divided into either the PT group or the non-PT group, based on whether they had received PT in 2016. The primary outcome was the number of respiratory tract infection episodes in 2017 and 2018. Descriptive statistics and negative binomial regression analyses were used to examine the associations between PT and the outcomes. The data for Study II and III were collected simultaneously through semi-structured qualitative interviews. The participants were caregivers (n=16) whose children with RRTIs had participated in a one-month-long PT trial. Reflexive thematic analysis was used to analyze the data. The analysis of the data was informed by embodiment theory in Study I and the concept of child-centered care in Study II. Study IV explored PT practice in the treatment of children with RRTIs through semi-structured interviews with thirteen PT practitioners. Reflexive thematic analysis was used, informed by the concept of child-centered care.Results: Children who underwent PT at least six times in 2016 experienced fewer episodes of acute respiratory tract infections (ARTIs) in 2017 (IRR: 0.59, 95% CI: 0.42-0.84) and 2018 (IRR: 0.58, 95% CI: 0.36-0.94) compared to those who did not receive PT. They also had fewer outpatient visits for ARTIs in 2017 (IRR: 0.56, 95% CI: 0.38-0.83). However, there was no significant difference between the two groups in terms of the number of outpatient antibiotic prescriptions (Study I). Caregivers evaluated PT by listening to others' experiences and closely observing both the techniques applied to their children's body and their children's physical responses during sessions. They also attentively monitored bodily changes in the children after the treatment. Through PT, an embodied attachment between children and both caregivers and practitioners was fostered. Compared to other treatments or medical consultations, children appeared more relaxed and actively engaged in this form of embodied care, which involved direct skin contact and verbal interaction with the Tuina provider. Additionally, children integrated PT into family life by requesting caregivers to perform it on them and imitating the techniques on their caregivers' hands (Study II). Caregivers seek PT as part of a proactive, child-centered approach to selecting appropriate care for their sick children. When symptoms are mild, they prefer self-learning and home remedies to avoid hospital visits. Caregivers favor healthcare providers who offer personalized treatment plans and display a positive attitude. Given the recurrent and prolonged nature of RRTIs and access to various healthcare options, they often adopt a combined approach-using biomedicine for symptom relief and Chinese medicine to address underlying causes. Additionally, they are cautious about long-term medication use, particularly antibiotics, and may discontinue prescribed treatments based on their own assessment (Study III). PT Practitioners assessed each child's condition to determine whether PT was appropriate, ensuring it would not delay essential biomedical care. If PT was deemed suitable, they carefully chose acupoints and techniques that were tailored to the child's individual needs. During the treatment, practitioners engaged in discussions with caregivers to gain a deeper understanding of the root causes of the child's RRTIs. They also communicated directly with the children to encourage their cooperation both before and during the session. Additionally, practitioners built a relationship with the children by staying fully present and attentive throughout the treatment process (Study IV).Conclusions:Findings from this thesis indicate that PT is more than just a clinical intervention for children's RRTIs in Southern China. It also plays a vital role in supporting children's overall wellbeing and fostering their relationship with the adults who provide PT, whether they are caregivers or practitioners. Children who receive six or more sessions of PT within a year may have fewer infections in the following two years. Additionally, PT could provide support in the home for caregivers of children with RRTIs, as it may enhance embodied care. Caregivers' motivation in seeking PT highlights the broader interest in child-centered care for children with RRTIs. It is therefore crucial for healthcare providers to foster good communication, tailor the treatment, and respect cultural beliefs. In PT practitioners' practice, child-centered care is exemplified by focusing on children's medical needs while fostering a good relationship with them. Approaches observed within a context of medical pluralism offer valuable insights into the core principles of child-centered care, enhancing our understanding of its fundamental elements.List of scientific papersI. Yin L, Stålsby Lundborg C, Wu D, Yang J, Alvesson HM, Cai J, Lu T, Qian X, Marrone G. Effect of pediatric Tuina on children's recurrent acute respiratory tract infections: a retrospective cohort study in Southern China. Journal of Traditional Chinese Medicine, 2024, 44(3), 586. https://doi.org/http://doi.org/10.19852/j.cnki.jtcm.2024.03.003Il. Yin L, Chang B, Stålsby Lundborg C, Wu D, Alvesson HM. "She mimicked the manipulations on my hand": fostering embodied care among children with recurrent acute respiratory tract infections in Southern China. BMC Complementary Medicine and Therapies, 2024, 24(1): 359. https://doi.org/http://doi.org/10.1186/s12906-024-04660-6III. Yin L, Chang B, Wu D, Stålsby Lundborg C, Alvesson HM. A child-centered approach: Caregivers' motivations for seeking pediatric Tuina for children's recurrent respiratory tract infections in Southern China. [Manuscript]IV. Yin L, Liu Y, Liao X, Wu D, Stålsby Lundborg C, Alvesson HM. "Children's comfort matters": Pediatric Tuina practitioners' experiences of treating children with recurrent respiratory tract infections in Southern China. [Manuscript]